Liquefied petroleum gas(LPG)storage design - Jonatan, Jacqlyn (2012)
Liquefied Petroleum Gas(LPG)is common fuel used for domestics, industrial and commercial appliances in Malaysia. Homes in Malaysia get LPG cylinders in various sizes offered by supplier,but most of them using 14kg cylinder.Generally, LPG composed of volatile low boiling point gases – ethane, propane,propene,iso-butane,n-butane,but-1-ene,iso-butene, trans-2-butene,cis-2-butene,and also iso-pentane and n-pentane due to the availability of higher boiling point components.When LPG is used,the low boiling point components will evaporate and the high boiling point components will stay in the cylinder.The research aimes to design an exploratory instrumentation for liquid LPG sampling under pressure,to explore the composition of liquid LPG in the LPG cylinder used in Malaysia and conclude whether some of the product might stay in the cylinder as liquid component after the volatiles are used.When the availability of high boiling point components which in turn will stay in the cylinder after it is empty from low boiling point components was proved,the research aimes to recommend a new idea for LPG cylinder design that is more energy-efficient.The first stage of the research was to design the easy and safe exploratory instrumentation for liquid LPG sampling under pressure and collect a sample.Then,the second stage is to determine the LPG composition using the available gas chromatography(GC)column available in FKKSA laboratory.The composition analysed and the retention time then compared to the reference for each of the expected substances to be exist in the LPG mixtures.The third stage is to propose a new design of LPG cylinder based on the existence of liquid component LPG in the LPG cylinder.The design is proposed based on the existence of the liquid LPG in used up LPG cylinder in Malaysia.